Trzy książki w jednym tomie: historia, analiza i antologia życia kulturalnego w Buchenwaldzie. Magdalena Izabela Sacha: „Gdyście w obóz przybyć już raczyli…”. Obraz kultury lagrowej w świadectwach więźniów Buchenwaldu 1937–1945. Bydgoszcz–Gdańsk... - Wolski, Paweł (Narracje o Zagładzie [czasopismo zamknięte], 2015)
Trzy książki w jednym tomie: historia, analiza i antologia życia kulturalnego w Buchenwaldzie. Magdalena Izabela Sacha: „Gdyście w obóz przybyć już raczyli…”. Obraz kultury lagrowej w świadectwach więźniów Buchenwaldu 1937–1945. Bydgoszcz–Gdańsk, Wydawnictwo Instytut Pamięci Narodowej, 2014, ss. 508 + 8 s. wkł. zdj. Three books in one: history, analysis and anthology of cultural life in Buchenwald Magdalena Izabela Sacha: „Gdyście w obóz przybyć już raczyli…”. Obraz kultury lagrowej w świadectwach więźniów Buchenwaldu 1937–1945. Bydgoszcz–Gdańsk, Wydawnictwo Instytut Pamięci Narodowej, 2014, ss. 508 + 8 s. wkł. zdj. The text discusses Magdalena Sacha’s approach to the issue of cultural activity in death and labour camps in her book „Gdyście w obóz przybyć już raczyli…”. Obraz kultury lagrowej w świadectwach więźniów Buchenwaldu 1937–1945. It consists of three parts: a historical introduction of major death and labour camps in the Third Reich, an analysis of the cultural production in Buchenwald and an anthology of poetry created in Buchenwald and HASAG‑Leipzig camps. The author of the article argues that Sacha’s seemingly traditional approach to historiography is deeply involved in the methodology introduced by New Historicism.